Arts and Crafts: Critical to Economic Innovation. (August 2013) - LaMore, Rex; Root-Bernstein, Robert; Root-Bernstein, Michele; Schweitzer, John H.; Lawton, James L.; Roraback, Eileen; Peruski, Amber; VanDyke, Megan; Fernandez, Laleah
Governments, schools, and other nonprofit organizations are engaged in critical budget decisions that may affect our economic development success. The assumption is that arts and crafts are dispensable extras. Research suggests, however, that disposing of arts and crafts may have negative consequences for the country's ability to produce innovative scientists and engineers who invent patentable products and found new companies. A study of Michigan State University Honors College science and technology graduates (1990-1995) yielded four striking results: (a) graduates majoring in science, technology, engineering, and mathematics (STEM) subjects are far more likely to have extensive arts and crafts skills than the average American; (b) arts and crafts experiences are significantly correlated with producing patentable inventions and founding new companies; (c) the majority believe that their innovative ability is stimulated by their arts and crafts knowledge; and (d) lifelong participation and exposure in the arts and crafts yields the most significant impacts for innovators and entrepreneurs.